The synthesis and highly effective antibacterial properties of Cu-3, 5-dimethy l-1, 2, 4-triazole metal organic frameworks - Xu, Xiaolin; Ding, Mengna; Liu, Kaiquan; Lv, Fujian; Miao, Yingchun; Liu, Yanmi; Gong, Ying; Huo, Yuning; Li, Hexing (Frontiers in Chemistry, 2023)
The influence of metal ions, the state of metal salt, and ligands on the sterilization ability of (Metalorganic frameworks) MOFs to effectively achieve sterilization has been investigated in this study. Initially, the MOFs were synthesized by elements of Zn, Ag, and Cd for the same periodic and main group of Cu. This illustrated that the atomic structure of Cu was more beneficial for coordinating with ligands. To further induce the maximum amount of Cu2+ ions in the Cu-MOFs to achieve the highest sterilization, various Cu-MOFs synthesized by the different valences of Cu, various states of copper salts, and organic ligands were performed, respectively. The results demonstrated that Cu-MOFs synthesized by 3, 5-dimethyl-1, 2, 4-triazole and tetrakis (acetonitrile) copper(I) tetrafluoroborate presented the largest inhibition-zone diameter of 40.17 mm towards Staphylococcus Aureus (S. aureus) under dark conditions. The proposed mechanism of Cu (Ⅱ) in MOFs could significantly cause multiple toxic effects, such as the generation of reactive oxygen species, and lipid peroxidation in S. aureus cells, when the bacteria was anchored by the Cu-MOFs via electrostatic interaction. Finally, the broad antimicrobial properties of Cu-MOFs against Escherichia coli (E. coli), Acinetobacter baumannii (A. baumannii), and S. aureus were demonstrated. In conclusion, the Cu-3, 5-dimethyl-1, 2, 4-triazole MOFs appeared to be potential antibacterial catalysts in the antimicrobial field.